The taste of traditions: flour as a cultural processof preparing food - Ludmilla Maria Lima Santos; Gerlane Ferreira da Silva (Universidade Estadual de Alagoas, 2021)
The work presented here rescues the production process of cassava flour in its socioeconomic cultural elements in the face of the current conjuncture of fierce contradictions caused by the great technological production of food and, in contrast, the perpetuation of hunger on a global scale. Based on the presented scenario, the main objective is to analyze, in view of the current conjuncture of development of the food industry and in return for the persistence of hunger, the cultural aspect of food preparation such as manioc flour. To this end, we intend to address issues such as: the process in which the preparation of cassava flour becomes the cultural tradition of flour and identify how the economic and social aspects are related to these cultural traditions of food preparation and consumption. For the construction of the text, bibliographical and documentary research was carried out, where the productions were analyzed based on the observation of the community daily life of rural communities in the municipality of Arapiraca, agresta Alagoas, among which the Remaining Community of Quilombo Carrasco. Emphasizing, in the midst of the contradictions and disparities of the contemporary food industry, a tradition such as the "floured ones, of great importance for the food and culture that has endured for generations, the present study, although still succinct, tends to boost the process of politicization of the act to eat in its multiple aspects in response to the increasingly current practices of violating the human right to quality food and food sovereignty and security.